2010
DOI: 10.1111/j.1751-553x.2009.01189.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA Index in childhood acute lymphoblastic leukaemia: a karyotypic method to validate the flow cytometric measurement

Abstract: The DNA index (DI) is a prognostic factor in childhood acute lymphoblastic leukemia (ALL). The accuracy of DI measurement is important for treatment stratification: hyperdiploidy with DI > or = 1.16 is predictive of favorable prognosis whereas hypodiploidy is associated with poor prognosis. The aim of this study was to validate the accuracy of the DI measured by flow cytometry (FCM) by comparison with the karyotype. From samples of 112 childhood ALL, we created a formula to calculate a theoretical DNA index (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 24 publications
(40 reference statements)
1
28
1
1
Order By: Relevance
“…In order to assess the validity of the DIs measured in each center (mDIs), the theoretical DIs (thDIs) were calculated when feasible, ie, when all chromosome gains were clearly identified on karyotypes. 8 Criteria for eligibility. Karyotypes presenting both a modal number ranging from 51 to 67 and a classical profile of chromosome gains of HD.50 were included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess the validity of the DIs measured in each center (mDIs), the theoretical DIs (thDIs) were calculated when feasible, ie, when all chromosome gains were clearly identified on karyotypes. 8 Criteria for eligibility. Karyotypes presenting both a modal number ranging from 51 to 67 and a classical profile of chromosome gains of HD.50 were included.…”
Section: Methodsmentioning
confidence: 99%
“…7 In HD.50, DIs range from 1.10 to 1.45, and the cutoff 1.16 corresponds to MNC 53 or 54. 7,8 The first study showing that outcome is heterogeneous within HD.50 has been based on DI. 7 This study has established that The online version of this article contains a data supplement.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, interphase fluorescence in situ hybridization or DNA indexing by flow cytometry may be used (Table 1). 21 Notably, masked near-haploid cases are readily detectable by SNP array analysis as having LOH involving all chromosomes that are not gained, whereas high-hyperdiploid cases mostly will display retained heterozygosity (Table 1). 19,22 Thus, as SNP array analysis and, in the future, next-generation sequencing are increasingly being used for genetic testing of ALL, the risk of misclassifying masked near-haploid cases will decrease.…”
Section: The Diagnostic Challenge Of Masked Hypodiploidymentioning
confidence: 99%
“…Chromosome numbers below 40 display a clear bimodal distribution, with peaks at 27 and 36 chromosomes, corresponding to the nearhaploid and low-hypodiploid subtypes, respectively ( Figure 1). In near-haploid ALL, retained disomies primarily comprise chromosomes X/Y, 8, 10, 14, 18, and 21, whereas retention of disomies X/Y, 1,5,6,8,10,11,14,18,19,21, and 22 is seen in low hypodiploid ALL (Figure 1). Notably, chromosome 21 is always retained in both groups.…”
Section: Introductionmentioning
confidence: 99%
“…Rachieru‐Sourisseau et al . reported that three of 112 patients with near‐triploidy/hyperploidy were identified as having hypodiploid karyotype only when flow cytometry (DNA index) was used . There were fewer cases of hypodiploid ALL in the present cohort than in studies performed in other countries, possibly because use of conventional karyotyping alone may have missed some cases of true hypodiploid ALL.…”
Section: Discussionmentioning
confidence: 59%